1972
DOI: 10.1139/v72-151
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Conditions for the Suppression of CH3 + Sb(CH3)2→Sb(CH3)3 and Evaluation of D[(CH3)2Sb—CH3]

Abstract: The pyrolysis of trimethylantimony has been studied in a toluene carrier flow system over the temperature range 690-803 K (total pressures 3.6-173.4 mm, contact times 1.0-13.5 s, decomposition 3.9-89.5%). The progress of the reaction was followed by measuring the amount of methane, ethane, and ethylbenzene formed. In 23 runs the undecomposed alkyl was also determined. The quantity found was in agreement with that expected from the product analysis if three methyl radicals are released for each molecule undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…The addition of azomethane (CH 3 N) 2 as a "clean" source of methyl radicals retards the TMSb decomposition slightly. This supports a reversible step in TMSb pyrolysis (reaction 7) that was previously reported [18]. Overall, homolytic fission of the Sb-C bonds in TMSb followed by normal free-radical reactions appears to describe the pyrolysis of TMSb under these conditions.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The addition of azomethane (CH 3 N) 2 as a "clean" source of methyl radicals retards the TMSb decomposition slightly. This supports a reversible step in TMSb pyrolysis (reaction 7) that was previously reported [18]. Overall, homolytic fission of the Sb-C bonds in TMSb followed by normal free-radical reactions appears to describe the pyrolysis of TMSb under these conditions.…”
Section: Resultssupporting
confidence: 88%
“…The resulting rate constants for TVSb and TIPSb derived from the Arrhenius plots are shown in eq 2 and 3, respectively. The activation energy for TVSb decomposition derived from eq 2 (49.0 kcal/mol) is less than the reported Sb-C bond energy for TMSb (55.9 kcal/mol) [18]. The activation energy for TIPSb decomposition derived from eq 3 (30.8 kcal/mol), which may represent the Sb-C bond strength in TIPSb, is substantially lower than for TMSb and TVSb.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…This study indicates that the decomposition mechanism of TMSb is similar to that of TMG in that it proceeds via bond scission and subsequent radical reactions to yield monomethyl antimony (MMSb, SbCH 3 ) and methyl radicals with an apparent activation energy of 55.9 kcal/mol [11]. It was again concluded that the active species in the radical chain reactions carried out in a H 2 or D 2 carrier gas were atomic hydrogen or deuterium [11,12].…”
Section: Previous Studies For Tmg/tmsbmentioning
confidence: 73%
“…This discrepancy could be reconciled under conditions of low Ga species surface coverage (K Ga P Ga 51), an assumption not explicitly stated by the authors. Furthermore, other kinetic studies of the decomposition of TMSb under a variety of conditions show no evidence of gas-phase Sb 4 formation [10][11][12]. Additionally, studies of the decomposition of TMG indicate that it is highly unlikely that TMG will decompose to Ga in the gas phase under typical MOVPE reactor residence times, pressures and temperatures [10,13,14].…”
Section: Previous Studies For Tmg/tmsbmentioning
confidence: 99%